Characterization of Placental Microvascular Architecture by MV‐Flow Imaging in Normal and Fetal Growth–Restricted Pregnancies. (19th October 2020) - Chen, Xinlin; Wei, Xia; Zhao, Sheng; Huang, Hui; Wang, Weiyun; Qiu, Junyu; Chen, Xiao; Cheng, Chen; Tian, Zhiyun; Rychik, Jack
Abstract : Objectives: To observe the microvascular architecture in the placental bed and explore the feasibility and clinical utility of MV‐Flow imaging (Samsung Medison Co, Ltd, Seoul, Korea) during normal pregnancy and fetal growth restriction (FGR). Methods: Placental microvascular structure ultrasound imaging by MV‐Flow was performed on 227 unaffected and 17 FGR fetuses between 11 and 41 weeks' gestation. A placental vascular index (VI MV ) was acquired by application of various MV‐Flow regions of interest (ellipse, rectangle, and manual trace). Unaffected control and FGR groups were assessed for umbilical artery, middle cerebral artery, and uterine artery pulsatility indices and the cerebroplacental ratio calculated by ultrasound. Results: No significant difference in the VI MV by varying regions of interest or placental regions was observed in the control group. The VI MV in the first trimester was lower than that in the second and third trimesters, with 5th through 95th percentile normal VI MV reference values of 18.39 to 63.79 for 13.6 weeks and earlier, 28.53 to 66.64 for 14 weeks to 27 weeks 6 days, and 21.95 to 67.45 for 28 weeks and later. The VI MV values in the FGR group were lower than those in the control group in the upper, middle, and lower parts of the placenta (mean ± SD, 24.9 ± 13.9 versus 45.0 ± 13.4; P  < .01; 30.5 ± 16.1 versus 44.7 ± 14.3; P  < .01; and 29.9 ± 17.4 versus 47.6 ± 12.2; P  < .01, respectively). Higher umbilical artery and uterine artery pulsatility indices and a lower cerebroplacental ratio were found in the FGR group compared with the control group ( P  < .01). Conclusions: MV‐Flow technology can display and quantify placental microvascular architecture at the level of the stem villi and villous leaves, and the VI MV provides for quantification of tissue vascularity. MV‐Flow is a potentially powerful and promising tool to explore placental microvascular perfusion and provide new information on a host of pregnancy‐related conditions.